The Multilevel Study on the Impact of High-Performance Human Resource Practices on Employees’ Voice Behavior: A Moderated Mediation Model - Liu, Yuanyuan; Liu, Dongxu; Du, Hui; Liu, Shuzhen; Zhou, Xiaoxue (Frontiers in Psychology, 2022)
Based on the social identity theory, the relationship and influencing mechanism between high performance human resource practices (HPHRPs) and employees’ voice behavior were explored by constructing a moderated mediation model, and the relationship between the field of human resources and the field of organization behavior was also established. Through 1178 paired samples of supervisor-employee survey and multi-level linear model analysis technology, it was found that: (1) HPHRPs had a positive impact on employees’ voice behavior; (2) Perceived insider status played a mediating role between HPHRPs and voice behavior; (3) Voice efficacy played a moderating role between perceived insider status and voice behavior; (4) Voice efficacy played a mediating role in the relationship between “HPHRPs - perceived insider status - voice behavior”.